Frequency of dendritiform inflammatory cells in the cornea in herpetic anterior uveitis without clinical keratitis and Fuchs uveitis - Knoll, Alexandra; Postole, Andreea-Silvia; Auffarth, Gerd U.; Mackensen, Friederike (Journal of ophthalmic inflammation and infection, 2014)
Herpetic anterior uveitis is a frequent cause of infectious uveitis. A definite diagnosis is obtained by anterior chamber puncture and polymerase chain reaction, an invasive procedure. We hypothesized that patients with herpetic anterior uveitis have a certain pattern of inflammatory cells in their cornea that distinguishes herpetic anterior uveitis from other uveitis types. This study is a prospective, controlled, observational study. Ten patients are with active herpetic anterior uveitis and 14 patients are with Fuchs uveitis syndrome. Patients were imaged with the Heidelberg Retina Tomograph with the Rostock Cornea Module attachment. Three images of the subepithelial area of the cornea were evaluated for dendritiform inflammatory cells. Means were calculated and used for analysis. The contralateral unaffected eyes and numbers published in the literature served as controls.